Axial spondyloarthritis: new advances in diagnosis and management. (4th January 2021) - Ritchlin, Christopher; Adamopoulos, Iannis E
Abstract: Axial spondyloarthritis (axSpA) is an inflammatory disease of the axial skeleton associated with significant pain and disability. Previously, the diagnosis of ankylosing spondylitis required advanced changes on plain radiographs of the sacroiliac joints. Classification criteria released in 2009, however, identified a subset of patients, under the age of 45, with back pain for more than three months in the absence of radiographic sacroiliitis who were classified as axSpA based on a positive magnetic resonance imaging or HLAB27 positivity and specific clinical features. This subgroup was labeled non-radiographic (nr)-axSpA. These patients, compared with those identified by the older New York criteria, contained a larger percentage of women and demonstrated less structural damage. However, their clinical manifestations and response to biologics were similar to radiographic axSpA. The discovery of the interleukin (IL) IL-23/IL-17 pathway revealed key molecules involved in the pathophysiology of axSpA. This discovery propelled the generation of antibodies directed toward IL-17A, which are highly effective and demonstrate treatment responses in axSpA that are similar to those observed with anti-TNF agents. The finding that agents that block IL-23 were not effective in axSpA came as a surprise and the potential underlying mechanisms underlying this lack of response are discussed. New agents with dual inhibition of the IL-17A and F isoforms and some oral small molecule agents that target the Jak-STAT pathway, have also shown efficacy in axSpA.